El afianzamiento de un precario comercio: los intercambios entre Sevilla y Yucatán (1590-1600) - García Bernal, Manuela Cristina (El Colegio de México, A.C., 2000)
This work underlines the importance of Yucatan's commercial relations across the Atlantic Ocean, as opposed to the traditional belief  that  these exchanges were small and  infrequent. Due to the margination and poverty of the province, in 1590 the Spanish Crown granted Yucatan a license  to send two small  ships each year, with the necessary products. This license  allowed the securing of a trade that until  then had  been quite  precarious. This is why the quantitative and qualitative analyses of the movements of ships and merchandise between 1590 and 1600 lets us understand why, despite being considered secondary, this region's commerce occupied, as seen from Seville, a considerable position among the  great amount of Atlantic trade. These analyses also reveal  why  during the  seventeenth  century Yucatan would come  to be  the  most  favored of the smaller posts along the Spain-Indies trading route.